Epidemiological Profile of Donation Candidates at a Pediatric Heart Transplant Reference Center - Sturm, Ana Laura Camargo (2025)
Introduction:  Heart transplantation is the standard treatment for end-stage heart disease. This therapy is limited by factors related to both the donor and the recipient, in addition to peculiarities inherent to its implementation in the pediatric population. Due to the disparity between organ supply and demand, heart transplant waiting list mortality is high in this age group, ranging from 17 to 30% worldwide. Even so, around 40% of listed hearts are not used worldwide. High refusal rates are due to the lack of uniformity in assessment, as well as in the acceptance and refusal of organs in pediatric heart transplantation. It is known that donor and recipient factors interact with each other in a complex way, requiring a joint analysis to determine whether the organ available at that time is suitable for the patient in question. Objectives:  To identify the epidemiological profile of candidates for heart donation offered to a pediatric heart transplant center in southern Brazil. Methods:  This is an observational, descriptive, and retrospective study. The sample consisted of medical records from potential donors offered from January 2021 to December 2023. Results:  There were 205 organs offered during this period, eight of which were excluded from the analysis due to a lack of data. The average age of the patients was 19.5 years and 67.5% of them were male. Chest radiography or tomography was not available in 38.6% of cases. A total of 56.3% of cases had an electrocardiogram available, but 45% of them were abnormal, and 29.4% of patients had no echocardiogram. Of the echocardiograms, 22.3% showed dysfunction. A total of 88.8% of patients were receiving vasoactive drugs and 61.9% had an active infection. Of the available organs, 92.9% were refused. Conclusion:  The refusal rate was higher than the global estimate, which may result from the lack of relevant donor-related information at the time of the offer. Moreover, there is a prevalence of data suggesting some degree of cardiac dysfunction in potential donors.